THE CONDITION OF VEGETATION MANGROVE IN BUNSUR VILLAGE SUNGAI APIT DISTRICT OF SIAK REGENCY RIAU PROVINCE - Muhammad Rafsan Zain; Efriyeldi Efriyeldi; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abtrac Mangroves are one of the important ecosystems in coastal areas that grow in places that are still affected by tides. This research was conducted in April 2018 in Bunsur Village, Sungai Apit District, Siak Regency. The purpose of this study is to determine the condition of the mangrove ecosystem in Bunsur Village which is seen from the density of mangroves, environmental quality indicators and the ecological index of the mangrove community. The method used in this research is survey method and the research used 3 stations. Environmental physics parameters were measured in situ, the results obtained in the research location were temperature 30-32 ° C, salinity 8-29 ‰, and pH 5-6. Data analysis was described in the form of tables and graphs of the environment including Avicennia alba, Bruguiera sp., Lumnitzera racemosa, Nypa fruticans, Rhizophora apiculata, Sonneratia alba, Xylocarpus granatum, and the density of mangrove farm 1 was 52566.67trees / hectare, station 2 was 55655.56 trees / hectare, station 3 was 22244.44 trees / hectare from the results of these densities on all mangrove stations classified as good (very dense) criteria. Indicator value of mangrove environmental quality at stations 1.2, and 3 ranged from 62.81 to 80.31% classified as high environmental quality.The value of the community ecological index sought includes diversity in which the results obtained in the three stations are 1.14-1.42 classified as low species. Uniformity index values ranged from 0.49 to 0.78, where at stations 1 and 3 are classified as balanced individual distributions and station 2 is classified as unbalanced individual distribution. Dominance index values ranged from 0.45 to 0.89, where station 1 was classified as low species dominance, station 2 was classified as medium species dominance, station 3 was classified as high species dominance. Keyword: Mangrove Vegetation Conditions, Sungai Apit